Risk Zone Mapping of Lead Pollution in Urban Groundwater - Siddique, Azhar; Zaigham, Nayyer A.; Mohiuddin, Shiekh; Mumtaz, Majid; Saied, Sumayya; Mallick, Khalil A. (Journal of Basic & Applied Sciences, 2012)
Groundwater samples (n = 230) were collected from various parts of the Karachi City (Pakistan), Karachi is an urban coastal City situated at the southern most part of the Pakistan along the Arabian Sea. The groundwater samples were subjected to electrothermal atomic absorption spectroscopy (EAAS) for the analysis of Pb. Variable Pb levels were observed in groundwater samples from different parts of the city. The relative higher concentrations of Pb were found in the industrial area of the Lyari River vicinity and along the coastal belt. GIS risk zone model based on disjunctive kriging were generated and areas associated with higher risk for Pb contamination were classified on the map. The outcomes of the study stressed that GIS spatial analysis could be a useful tool for the assessment and forecasting of health risk in complex urban environmental setup.